1992
DOI: 10.1111/j.1471-4159.1992.tb08362.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Melanin Complex in Substantia Nigra of Parkinsonian Brains: An X‐Ray Microanalysis

Abstract: Using energy-dispersive x-ray analysis on an electron microscope working in the scanning transmission electron microscopy mode equipped with a microanalysis system, we studied the subcellular distribution of trace elements in neuromelanin-containing neurons of the substantia nigra zona compacta (SNZC) of three cases of idiopathic Parkinson's disease (PD) [one with Alzheimer's disease (AD)] and of three controls, in Lewy bodies of SNZC, and in synthetic dopamine-melanin chemically charged or uncharged with Fe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(157 citation statements)
references
References 23 publications
7
150
0
Order By: Relevance
“…In the SN of PD patients, redox-active iron levels are increased by 30 -35% compared with age-matched controls (for review, see Zecca et al, 2004;Götz et al, 2004). Neuromelanin, a dark pigment produced in catecholaminergic neurons of the human SN and locus ceruleus, acts as a storage system for iron in dopaminergic neurons (Zecca et al, 2002) and has been found to associate with large amounts of iron in diseased nigral tissue (Jellinger et al, 1992(Jellinger et al, , 1993. Neuromelanin could potentially serve a neuroprotective function by sequestering free intracellular iron.…”
Section: Resultsmentioning
confidence: 99%
“…In the SN of PD patients, redox-active iron levels are increased by 30 -35% compared with age-matched controls (for review, see Zecca et al, 2004;Götz et al, 2004). Neuromelanin, a dark pigment produced in catecholaminergic neurons of the human SN and locus ceruleus, acts as a storage system for iron in dopaminergic neurons (Zecca et al, 2002) and has been found to associate with large amounts of iron in diseased nigral tissue (Jellinger et al, 1992(Jellinger et al, , 1993. Neuromelanin could potentially serve a neuroprotective function by sequestering free intracellular iron.…”
Section: Resultsmentioning
confidence: 99%
“…[84] Neuromelanin has been reported to have a dichotomous role (adverse or protective): beneficial when it reduces the oxidative stress in the brain due to its ability to bind cations; detrimental when it exacerbates the oxidative stress releasing H 2 O 2 or by reducing redox-active metals to a more reactive state. [85][86][87] Particular efforts have been made in understanding the binding of iron to neuromelanin, [76,[88][89][90][91][92][93][94][95] as iron was reported in dopaminergic neurons of Parkinsonian brains. [8] Recently, Sepia melanin has been identified as a suitable model to describe the binding characteristics of neuromelanin.…”
Section: Introductionmentioning
confidence: 99%
“…In the individuals with the L allele, the COMT protein is thermolabile. Decreased COMT activity may result in increased metabolism of dopamine to neuromelanin that can enhance the formation of cytotoxic radicals contributing to neuronal degeneration [21]. As the A allele of COMT G1947A is associated with low COMT activity of soluble COMT [37], the A allele of COMT G1947A may be linked to an increased risk of PD.…”
Section: Introductionmentioning
confidence: 99%